Outstanding Contributions of Limulus Amebocyte Lysate (LAL) Technology in Medical and Pharmaceutical Fields: Progress, Challenges and Future Directions - Hiroshi Tamura; Johannes Reich; Isao Nagaoka (Medical Science: Trends and Innovations Vol. 2, 2025)
In 1964, Levin and Bang first discovered that the lysate from Atlantic horseshoe crab (Limulus polyphemus) coagulated upon contact with bacterial endotoxins, and their epoch-making research findings contributed to the remarkable development of a test. Limulus amebocyte lysate (LAL) is an aqueous extract of horseshoe crab (Limulus polyphemus or Tachypleus tridentatus) blood cells. The blue blood of the horseshoe crab is a natural, irreplaceable, and precious resource that is highly valued by the biomedical industry. This review focuses on discussing the methods, progress, challenges, and future perspectives of LAL technology in the early detection and management of bacterial infections and invasive fungal diseases. LAL functions as a surprisingly sophisticated sensing system that allows for the extremely sensitive detection of bacterial and fungal cell-wall components owing to their remarkable sensitivity, quantitative accuracy and reproducibility with levels of as low as 1 pg/mL. Notably, LAL tests have markedly contributed to the quality control of pharmaceutical drugs and medical devices as successful alternatives to the rabbit pyrogen test. Furthermore, LAL-based endotoxin and (1\(→\)3)- \(β\)-D-glucan (\(β\)-glucan) assay techniques are expected to have optimal use as effective biomarkers, serving as adjuncts in the diagnosis of bacterial sepsis and fungal infections. The innovative \(β\)-glucan assay has substantially contributed to the early diagnosis and management of invasive fungal diseases with a high sensitivity of 70-90% and specificity of 79-100% from many clinical performance studies; however, the clinical significance of the endotoxin assay remains unclear and is challenging to elucidate. Many obstacles need to be overcome to enhance the analytical sensitivity and clinical performance of the LAL assay in detecting circulating levels of endotoxin in human blood. Consequently, improved techniques would be especially useful in demasking and capturing LPS molecules in circulating blood. Additionally, there are complex interactions between endotoxin molecules and blood components that are attributable to the unique physicochemical properties of lipopolysaccharide (LPS). In this regard, while exploring the potential of new LPS-sensing technologies, a novel platform for the ultrasensitive detection of blood endotoxin will enable a reappraisal of the LAL assay for the highly sensitive and reliable detection of endotoxemia.